Dermal fibroblasts induce cell cycle arrest and block epithelial–mesenchymal transition to inhibit the early stage melanoma development. (6th April 2016) - Zhou, Linli; Yang, Kun; Randall Wickett, R.; Zhang, Yuhang
Abstract: Stromal fibroblasts are an integral part of the tumor stroma and constantly interact with cancer cells to promote their initiation and progression. However, the role and function of dermal fibroblasts during the early stage of melanoma development remain poorly understood. We, therefore, designed a novel genetic approach to deactivate stromal fibroblasts at the onset of melanoma formation by targeted ablation of β ‐catenin. To our surprise, melanoma tumors formed from β ‐catenin‐deficient group (B16F10 mixed with β ‐catenin‐deficient fibroblasts) appeared earlier than tumors formed from control group (B16F10 mixed with normal dermal fibroblasts). At the end point when tumors were collected, mutant tumors were bigger and heavier than control tumors. Further analysis showed that there were fewer amounts of stromal fibroblasts and myofibroblasts inside mutant tumor stroma. Melanoma tumors from control group showed reduced proliferation, down‐regulated expression of cyclin D1 and increased expression of cyclin‐dependent kinase inhibitor p16, suggesting dermal fibroblasts blocked the onset of melanoma tumor formation by inducing a cell cycle arrest in B16F10 melanoma cells. Furthermore, we discovered that dermal fibroblasts prevented epithelial‐mesenchymal transition in melanoma cells. Overall, our findings demonstrated that dermal fibroblasts crosstalk with melanoma cells to regulate in vivo tumor development via multiple mechanisms, and the outcomes of their reciprocal interactions depend on activation states of stromal fibroblasts and stages of melanoma development. Abstract : We developed a novel genetic approach to deactivate stromal fibroblasts in vivo to determine their role and functions at the onset of melanoma formation. Our findings clearly suggest that dermal fibroblasts defend against melanoma during early stages of tumor formation by inducing a cell cycle arrest, partially through MAPK/ERK and pRB pathways, and blocking epithelial‐mesenchymal transition in melanoma cells.